Plant Water Stress Reduces Aphid Performance: Exploring Mechanisms Driven by Water Stress Intensity - Kansman, Jessica T.; Basu, Saumik; Casteel, Clare L.; Crowder, David W.; Lee, Benjamin W.; Nihranz, Chad T.; Finke, Deborah L. (Frontiers in Ecology and Evolution, 2022)
Drought alters plant traits in ways that affect herbivore performance. However, we lack a comprehensive understanding of the plant-derived mechanisms that mediate insect responses to drought. Water stress occurs along gradients of intensity, and the impacts of drought intensity on plant-insect interactions is understudied. Here, we assessed aphid performance on wheat plants exposed to a gradient of water stress and measured plant nutrients and phytohormones that may mediate aphid response to drought. We show that water stress reduced aphid performance, and the negative effect grew stronger as the magnitude of water stress increased. The plant response to water limitation was not consistent across the stress gradient and was reliant on the trait measured. Water limitation did not affect whole-plant nitrogen; however, water limitation did reduce amino acid concentration and increase sugars, but only under high stress intensity. The phytohormones abscisic acid (ABA), jasmonic acid (JA), and salicylic acid (SA), and the expression of their associated gene transcripts, were also differentially affected by water stress intensity. In well-watered conditions, aphid feeding increased concentrations of the defense-related hormones SA and JA over time; however, any amount of water limitation prevented aphid induction of JA. Although aphids may experience a reprieve from JA-related defenses in stressed conditions, SA levels remain high in response to aphid feeding, indicating aphids are still vulnerable to SA-related defenses. Any level of water stress also increased the expression of a callose-associated gene transcript, a physical defense that impairs feeding. Thus, poor aphid performance on mildly-stressed plants was correlated with increased plant defenses, whereas poor performance on highly-stressed plants was correlated with stronger plant defense induction and reduced plant nutritional quality. Understanding the mechanisms driving aphid and plant performance under water stress conditions can improve our ability to predict how aphid populations will respond to climate change.